Longitudinal Changes in Health-Related Quality of Life Among Older Adults Undergoing Hemodialysis - Wantonoro, Wantonoro; Suarni, Lisa; Novita, Dian; Van Nguyen, Tuan (Poltekkes Kemenkes Tanjung Karang, 2025)
Chronic kidney disease is a significant public health problem worldwide. Hemodialysis is the most common form of kidney replacement therapy in the world. Hemodialysis therapy is associated with deterioration in health-related quality of life. However, limited studies focused on health-related quality of life subscales among older persons with hemodialysis in the Indonesian population, especially with long-term follow-up. This study aims to explore the six-month longitudinal changes in health-related quality of life subscales among older persons with hemodialysis. This prospective cohort study evaluated 119 older adults undergoing hemodialysis using purposive sampling between March and September 2024 at PKU Yogyakarta Hospital, Indonesia. Outcomes status was evaluated with health-related quality of life at 1-, 3-, and 6-months. The Indonesian version of SF-36 assessed health-related quality of life. Data were analyzed using general estimating equations. In general, the health-related quality of life among older persons with hemodialysis was decreased. The longitudinal changes of eight subscales significantly deteriorated from the first month to the third month and remained consistently worse during the third to the sixth months (p=.001, respectively). Most deterioration was found in role limitation due to physical problem (β=-94.4; p=.001), general health (β=-70.5; p=.001), and vitality (β=-66.9; p=.001). Social function showed the better domain during the 6 months (β=-36.6; p=.001) than other health-related quality of life subscales. Different aspects of health-related quality of life deteriorate differently among older persons with hemodialysis. Specific attention needs to be paid to high-risk Indonesians among older persons with hemodialysis health-related quality of life, especially those who are older.